A Systematic Review of Inpatient Care Costs: Evaluating Cost Coverage and Financial Sustainability for Hospitals - Suarthana, Gede Made Wisnu; Musmini, Lucy Sri; Sinarwati, Ni Kadek (Jurnal Ilmiah Global Education, 2025)
The cost of inpatient hospital services is an important factor in the financial sustainability of health facilities. The ever-increasing cost of hospitalization poses a challenge to hospitals' financial sustainability, especially since the discrepancy between INA-CBG rates and actual costs often causes financial problems. This can reduce operational efficiency and service quality, particularly for vulnerable communities. This study to analyze the evaluation of the coverage of hospital care costs and financial sustainability. The methods A systematic review was conducted based on the PRISMA 2020 guidelines. Data were obtained from two main databases: Google Scholar and Garuda. A total of thirteen research articles met the inclusion criteria (articles from 2019–2024 that used the activity-based costing approach and were relevant to inpatient service rates). Quality assessment was conducted using the Newcastle-Ottawa Scale and internal validation questions. The results show that the ABC method provides a more accurate estimation of inpatient costs than the conventional method. There was a significant difference between the actual hospital rates and the ABC calculation results in the form of both under- and over-costing. Five studies showed lower rates than actual costs, while three studies showed higher rates. Conclusion: The application of ABC method is important for cost efficiency, fair tariff setting, and hospital financial stability and supports tariff negotiations with payers such as INA-CBGs.